Multivariable analysis of the influence of cross‐reactive carbohydrate determinant inhibition and other factors on intradermal and serological allergen test results: a prospective, multicentre study. Issue 4 (9th June 2021) - Canning, Peter; Brame, Bailey; Stefanovski, Darko; Lee, Kenneth W.; Cain, Christine L.; Rook, Katherine; Morris, Daniel O.
Abstract : Background: Serological allergen testing (SAT) is used widely to formulate allergen‐specific immunotherapy for atopic dogs. Serum immunoglobulin (Ig)E specific for cross‐reactive carbohydrate determinants (CCD) can produce false‐positive reactions, creating discrepancy between SAT and intradermal allergen test (IDAT) results. Objectives: The primary objective was to determine if inhibition of anti‐CCD IgE in a commercial assay improved correlation with IDAT. The secondary objective was to assess the influence of dog‐ and clinic‐specific factors, environmental factors, putative allergen exposure and prior medications on intradermal and SAT reactivity. Animals: Two‐hundred and eleven client‐owned dogs were enrolled from eight North American dermatology specialty practices. Methods and materials: Collection of serum samples and IDAT were performed on the same day. Sera were assayed for detection of IgE specific to 25 allergens, before and after treatment with a proprietary inhibitor of anti‐CCD IgE. Data for each dog were collected via a questionnaire filled out by veterinary personnel. Results: The correlation between the testing modalities was fair before (Spearman's rho, ρ = 0.2092) and after (ρ = 0.3042) inhibition of anti‐CCD IgE. Ciclosporin dose ( P  = 0.003), independent of duration of use, and duration of lokivetmab use ( P  = 0.001), independent of dose administered, were associated with statistically significant decreases in IgE concentrations across all allergen types. Conclusions and clinical relevance: Contrary to previous reports, this study demonstrated unchanged correlation between SAT and IDAT after inhibition of anti‐CCD IgE. Ciclosporin dose and lokivetmab treatment duration may have unexplored effects on IgE concentration during SAT. Abstract : Background – Serological allergen testing (SAT) is used widely to formulate allergen‐specific immunotherapy for atopic dogs. Serum immunoglobulin (Ig)E specific for cross‐reactive carbohydrate determinants (CCD) can produce false‐positive reactions, creating discrepancy between SAT and intradermal allergen test (IDAT) results. Objectives – The primary objective was to determine if inhibition of anti‐CCD IgE in a commercial assay improved correlation with IDAT. The secondary objective was to assess the influence of dog‐ and clinic‐specific factors, environmental factors, putative allergen exposure and prior medications on intradermal and SAT reactivity. Conclusions and clinical relevance – Contrary to previous reports, this study demonstrated unchanged correlation between SAT and IDAT after inhibition of anti‐CCD IgE. Ciclosporin dose and lokivetmab treatment duration may have unexplored effects on IgE concentration during SAT. Résumé: Contexte: Les tests allergologiques sériques (SAT) sont largement utilisés pour composer l'immunothérapie spécifique d'allergènes des chiens atopiques. Les immunoglobulines (Ig) E sériques spécifiques des CCD (cross‐reactive carbohydrate determinants) peuvent engendrer des faux positifs, créant un décalage entre les résultats des intradermoréactions (IDAT) et les SAT. Objectifs: Le premier objectif était de déterminer si l'inhibition des IgE anti‐CCD dans un test commercial, améliorait la corrélation avec les IDAT. Le deuxième objectif était d'évaluer l'influence des facteurs spécifiques des cliniques et des chiens, des facteurs environnementaux, de l'exposition potentielle aux allergènes et des traitements antérieurs sur la réactivité intradermique et SAT. Sujets: Deux cent onze chiens de propriétaires ont été inclus de huit services de dermatologie d'Amérique du Nord. Matériels et méthodes: La collecte des échantillons sériques et IDAT a été réalisée le même jour. Les sera ont été soumis à la détection d'IgE spécifiques de 25 allergènes, avant et après traitement avec un inhibiteur d'IgE anti‐CDD. Les données de chaque chien ont été collectées via un questionnaire rempli par le personnel vétérinaire. Résultats: La corrélation entre les modalités des tests était faible avant (Spearman's rho, ρ = 0.2092) et après (ρ = 0.3042) inhibition des IgE anti‐CCD. La dose de ciclosporine ( P  = 0.003), indépendamment de la durée d'utilisation, et la durée d'utilisation du lokivetmab ( P  = 0.001), indépendamment de la dose administrée, ont été associés à une diminution statistiquement significative des concentrations d'IgE pour tous les types d'allergènes. Conclusions et importance clinique: Contrairement aux publications antérieures, cette étude montre une corrélation inchangée entre SAT et IDAT après inhibition des IgE anti‐CCD. La dose de ciclosporine et la durée du traitement au lokivetmab pourraient voir des effets inexplorés sur les concentrations d'IGE au cours des SAT. Resumen: Introducción: la prueba serológica de alérgenos (SAT) se usa ampliamente para formular inmunoterapia específica de alérgenos para perros atópicos. La inmunoglobulina (Ig)E sérica específica para determinantes de carbohidratos de reacción cruzada (CCD) puede producir reacciones positivas falsas, creando discrepancias entre los resultados de SAT y la prueba intradérmica (IDAT). Objetivos: el objetivo principal era determinar si la inhibición de IgE anti‐CCD en un ensayo comercial mejoraba la correlación con IDAT. El objetivo secundario fue evaluar la influencia de factores específicos de la clínica y del perro, factores ambientales, exposición supuesta a alérgenos y medicamentos previos sobre la reactividad intradérmica y SAT. Animales: se inscribieron doscientos once perros de propietarios particulares de ocho clínicas especializadas en dermatología de América del Norte. Métodos y materiales: La recolección de muestras de suero y la IDAT se realizaron el mismo día. Se analizaron los sueros para la detección de IgE específica para 25 alérgenos, antes y después del tratamiento con un inhibidor patentado de IgE anti‐CCD. Los datos de cada perro se recopilaron a través de un cuestionario completado por personal veterinario. Resultados: la correlación entre las modalidades de prueba fue regular antes (rho de Spearman, ρ = 0, 2092) y después (ρ = 0, 3042) de la inhibición de la IgE anti‐CCD. La dosis de ciclosporina ( P = 0, 003), independientemente de la duración del uso y la duración del uso de lokivetmab ( P = 0, 001), independientemente de la dosis administrada, se asociaron con disminuciones estadísticamente significativas en las concentraciones de IgE en todos los tipos de alérgenos. Conclusiones y relevancia clínica: contrariamente a informes anteriores, este estudio demostró una correlación sin cambios entre SAT e IDAT después de la inhibición de IgE anti‐CCD. La dosis de ciclosporina y la duración del tratamiento con lokivetmab pueden tener efectos inexplorados sobre la concentración de IgE durante la SAT. Zusammenfassung: Hintergrund: Serologische Allergentests (SAT) werden weithin eingesetzt, um eine Allergen‐spezifische Immuntherapie für atopische Hunde zu formulieren. Serum Immunglobulin (Ig)E spezifisch für kreuzreaktive Kohlenhydratdeterminanten (CCD) können falsch‐positive Reaktionen verursachen, was eine Diskrepanz zwischen SAT und Intradermaltest (IDAT) Ergebnissen verursacht. Ziele: Das primäre Ziel war es festzustellen, ob die Inhibierung von anti‐CCD IgE in einem kommerziellen Assay die Korrelation mit IDAT verbessern würde. Das zweite Ziel war es, den Einfluss auf die Hunde‐ und Klinik‐spezifischen Faktoren, Umweltfaktoren, vermeintliche Allergenexponierung und frühere Medikationen auf die intradermale und die SAT Reaktivität zu beurteilen. Tiere: Zweihundertelf Hunde im Privatbesitz, die Patienten in acht Nordamerikanischen Dermatologie Spezialpraxen waren, wurden in die Studie aufgenommen. Methoden und Materialien: Es wurden Serumproben genommen und am selben Tag ein IDAT durchgeführt. Die Sera wurden vor und nach der Behandlung mit einem speziellen anti‐CCD IgE Inhibitor, auf spezifisches IgE auf 25 Allergene untersucht. Die Daten von jedem Hund wurden mittels Fragebogen, welcher durch das veterinärmedizinische Personal ausgefüllt wurde, erfasst. Ergebnisse: Die Korrelation zwischen den Testmodalitäten war moderat vor (Spearman´s rho, ρ = 0, 2092) und nach (ρ = 0, 3042) Inhibierung von anti‐CCD IgE. Die Ciclosporindosis ( P = 0, 003), unabhängig von der Dauer der Anwendung, die Dauer der Lokivetmab Anwendung ( P = 0, 001), unabhängig von der verabreichten Dosis, wurden mit statistisch signifikant niedrigeren IgE Konzentrationen auf alle Allergentypen in Zusammenhang gebracht. Schlussfolgerungen und klinische Bedeutung: Entgegen den früheren Berichten zeigte diese Studie nach der Inhibierung von anti‐CCD IgE eine unveränderte Korrelation zwischen SAT und IDAT. Die Ciclosporindosis und die Lokivetmab Behandlung könnte noch unerforschte Auswirkungen auf die IgE Konzentration während dem SAT haben. 要約: 背景: 血清学的アレルゲン検査 (SAT) は、アトピー犬のアレルゲン特異的免疫療法の処方に広く用いられている。交差反応性糖鎖決定基 (CCD) に特異的な血清免疫グロブリン (Ig)Eは偽陽性反応を示し、SATや皮内アレルゲン検査 (IDAT) の結果に矛盾を生じさせることがある。 目的: 第一の目的は、市販の検査法で抗CCD IgEを阻害することにより、IDATとの相関性が向上するかどうかを判断することであった。第二の目的は、皮内反応およびSAT反応に対する犬、診療所固有因子、環境因子、推定アレルゲン暴露および投薬歴の影響を評価することである。 供試動物: 北米の8つの皮膚科専門医院から、クライアント所有犬211頭が登録された。 材料と方法: 血清サンプルの収集とIDATは同日に行われた。血清は25のアレルゲンに特異的なIgEの検出のために、独自に開発した抗CCD IgE阻害剤による治療の前後で測定された。各犬のデータは、獣医師が記入したアンケートによって収集された。 結果: 検査方法間の相関は、抗CCD IgE阻害剤投与前(Spearman's rho, ρ = 0.2092)と投与後 (ρ = 0.3042)で良好であった。シクロスポリンの投与量 (P = 0.003) は使用期間とは無関係に、また、ロキベトマブの使用期間 (P = 0.001) は投与量とは無関係に、すべてのアレルゲンタイプにおいてIgE濃度の統計的に有意な低下と関連していた。 結論と臨床的妥当性: これまでの報告とは異なり、本研究では、抗CCD IgEを阻害した後もSATとIDATの相関性は変わらないことが示された。シクロスポリンの投与量およびlokivetmabの治療期間は、SAT中のIgE濃度に未解明の影響を及ぼす可能性がある。 摘要: 背景: 血清学过敏原检测(SAT)广泛用于制定特应性犬的过敏原特异性免疫治疗。交叉反应性碳水化合物决定簇(CCD)特异性血清免疫球蛋白(Ig)E可产生假阳性反应, 导致SAT和皮内过敏原试验(IDAT)结果之间的差异。 目的: 主要目的是确定在商业检测中抑制抗CCD IgE是否改善与IDAT的相关性。次要目的是评估犬和临床特异性因素、环境因素、假定过敏原暴露和既往用药对皮内和SAT反应性的影响。 动物: 211只客户拥有的犬来自北美的8个皮肤专科诊所。 方法和材料: 在同一天进行血清样本采集和IDAT。在用抗CCD IgE的专用抑制剂处理前后, 测定血清中25种过敏原特异性IgE的检测。通过兽医人员填写的调查问卷收集每只犬的数据。 结果: 抗CCD IgE抑制前(斯皮尔曼相关系数, ρ = 0.2092)和抑制后(ρ = 0.3042), 检测方式之间的相关性一般。环孢素剂量(P = 0.003)与使用持续时间和洛基维特单抗使用持续时间(P = 0.001)无关, 与给药剂量无关, 与所有过敏原类型中IgE浓度的统计学显著性降低相关。 结论和临床相关性: 与之前的报告相反, 本研究表明抗CCD IgE抑制后SAT和IDAT之间的相关性不变。在SAT期间, 环孢素剂量和洛基维特单抗治疗持续时间可能对IgE浓度的影响尚需探索。 Resumo: Contexto: O teste sorológico de alérgenos (TAS) é amplamente utilizado para formular imunoterapia alérgeno‐específica para cães atópicos. A imunoglobulina (Ig)E sérica específica para determinantes de carboidratos de reação cruzada (CCD) pode produzir reações falso‐positivas, criando discrepância entre os resultados do TAS e do teste de alérgeno intradérmico (TAID). Objetivos: O objetivo principal era determinar se a inibição de IgE anti‐CCD em um ensaio comercial melhorava a correlação com o TAID. O objetivo secundário foi avaliar a influência de fatores específicos do cão e da clínica, fatores ambientais, suposta exposição a alérgenos e medicamentos anteriores na reatividade intradérmica e TAS. Animais: Duzentos e onze cães de propriedade de clientes foram inscritos em oito clínicas de especializadas dermatologia norte‐americanas. Métodos e materiais: A coleta das amostras de soro e o TDAI foram realizadas no mesmo dia. Os soros foram testados para detecção de IgE específica para 25 alérgenos, antes e depois do tratamento com um inibidor patenteado de IgE anti‐CCD. Os dados de cada cão foram coletados por meio de um questionário preenchido pela equipe veterinária. Resultados: A correlação entre as modalidades de teste foi razoável antes (rho de Spearman, ρ = 0, 2092) e após (ρ = 0, 3042) a inibição de IgE anti‐CCD. A dose de ciclosporina (P = 0, 003), independente da duração do uso e a duração do uso de lokivetmab (P = 0, 001), independente da dose administrada, foram associadas a diminuições estatisticamente significativas nas concentrações de IgE em todos os tipos de alérgenos. Conclusões e relevância clínica: Ao contrário de relatos anteriores, este estudo demonstrou correlação inalterada entre TAS e TAID após a inibição de IgE anti‐CCD. A dose de ciclosporina e a duração do tratamento com lokivetmab podem ter efeitos inexplorados na concentração de IgE durante o TAS.